EFIKASI DAN KEAMANAN MANAJEMEN PENGOBATAN MEDIS OVERACTIVE BLADDER: A MINI-LITERATURE REVIEW - Dalri Muhammad Suhartomo; Synta Haqqul Fadlillah; Indra Yudhawan (Medical and Health Journal, 2022)
Overactive bladder (OAB) is a widespread condition that significantly impairs one's quality of life, yet it often goes undiagnosed and is treated inadequately due to various obstacles such as shame, poor communication, and poor patient compliance. There are several treatment options for OAB, including bladder and behavioural training, medications, and surgical therapies. Oral antimuscarinics are the primary choice for pharmacological treatment of OAB. There are a variety of drugs available to treat bladder storage and voiding issues, and soon, novel compounds with higher specificity for the lower urinary tract receptors will be available. This will help to optimize therapy, reducing side effects and improving adherence, particularly in patients with existing medical conditions and in women. This article provides an overview of the pharmacotherapy of OAB.